The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1104/pp.110.4.1367
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Reactive Oxygen Species, Glutathione Metabolism, and Lipid Peroxidation in the Cf-Gene-Dependent Defense Response of Tomato Cotyledons Induced by Race-Specific Elicitors of Cladosporium fulvum

Abstract: The chronological order of responses to Cladosporium fulvum (Cooke) (Cf) race-specific elicitors was assessed in cotyledons of three near-isogenic tomato (Lycopersicon esculentum Mill.) lines carrying either Cf-9 or Cf-2 or no Cf gene. The responses observed were dependent on the presence of a Cf gene, Avr-gene product dose injected, and the relative humidity (RH) of the growth chamber. At ambient RH, superoxide formation and lipid peroxidation occurred after 2 h (Cf9) and 4 h (Cf2). At elevated RH (98%) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(121 citation statements)
references
References 59 publications
5
116
0
Order By: Relevance
“…For example, certain puri®ed elicitors can induce many of the physiological changes occurring during disease resistance (Nu È rnberger et al, 1994) and lesions resembling the HR (He et al, 1993;May et al, 1996). Therefore the destructive potential of an active pathogen is not necessary.…”
Section: Is the Hr Programmed?mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, certain puri®ed elicitors can induce many of the physiological changes occurring during disease resistance (Nu È rnberger et al, 1994) and lesions resembling the HR (He et al, 1993;May et al, 1996). Therefore the destructive potential of an active pathogen is not necessary.…”
Section: Is the Hr Programmed?mentioning
confidence: 99%
“…A membrane NADPH oxidase analogous to that found in mammalian neutrophils may be involved in this process (Groom et al, 1996). ROIs could also act as a signal via the production of lipid peroxides (May et al, 1996;Mehdy, 1994). The XR is characterized by an uptake of Ca 2+ (Levine et al, 1996) and export of Cl 7 and K + driven by H + -ATPases, resulting in alkalinization of the cytoplasm (Atkinson and Baker, 1989).…”
Section: How Is the Hr Induced?mentioning
confidence: 99%
See 1 more Smart Citation
“…The delay could be explained by inherent antioxidant mechanisms within the plant cells that were able to counter any initial H 2 O 2 burst induced by the low concentration of Nep1. May et al [53] measured induced responses in near-isogenic lines of tomato by race-specific A6r-gene products from C. ful6um. The elicitors induced the production of reactive oxygen species, including H 2 O 2 , and caused increases in glutathione levels and lipoxygenase enzyme activity.…”
Section: Cell Culture Experimentsmentioning
confidence: 99%
“…In plants, this response is termed the hypersensitive response (HR) and results in the formation of a zone of dead cells around the infection site, the synthesis of salicylic acid (SA), and the accumulation of antimicrobial agents, such as pathogenesis-related (PR) proteins and phytoalexins (Goodman and Novacky, 1994;Dangl et al, 1996; HammondKosack and Jones, 1996). The layers of dead cells that surround the site of pathogen entry are thought to function as a physical barrier that inhibits further proliferation and spread of the pathogen (Goodman and Novacky, 1994).PCD that occurs during the HR is accompanied by an increase in the production of reactive oxygen species (ROS) and lipid peroxidation (Doke and Ohashi, 1988;Mehdy, 1994;Hammond-Kosack and Jones, 1996;May et al, 1996; Yang et al, 1997). Recent studies have indicated that reactive oxygen intermediates in the form of H 2 O 2 and are key mediators of PCD during the HR (Levine et al, 1994, O 2 • Ϫ 1996; Jabs et al, 1996;Draper, 1997;Shirasu et al, 1997) and may function as part of a signal transduction pathway leading to the induction of PR proteins and systemic resistance in infected and noninfected parts of the plant (Chen et al, 1993;Green and Fluhr, 1995).…”
mentioning
confidence: 99%